2019
DOI: 10.1002/jcb.28591
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of vimentin intermediate filaments in hypotonic stress

Abstract: Intermediate filaments (IFs) play a key role in the control of cell structure and morphology, cell mechano-responses, migration, proliferation, and apoptosis.However, the mechanisms regulating IFs organization in motile adhesive cells under certain physical/pathological conditions remain to be fully understood.In this study, we found hypo-osmotic-induced stress results in a dramatic but reversible rearrangement of the IF network. Vimentin and nestin IFs are partially depolymerized as they are redistributed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Consequently, the observed fast degradation of vimentin filaments, but not actin filaments or microtubules, under hypotonic stress cannot be explained through the intrinsic stabilities of the different filaments. A recent study proposes that microtubule‐based transport may mediate the reorganization of the vimentin cytoskeleton under hypotonic stress . We found that in our case, the fast degradation of the vimentin cytoskeleton persisted upon removal of the microtubule cytoskeletal system (Figure S5, Supporting Information).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Consequently, the observed fast degradation of vimentin filaments, but not actin filaments or microtubules, under hypotonic stress cannot be explained through the intrinsic stabilities of the different filaments. A recent study proposes that microtubule‐based transport may mediate the reorganization of the vimentin cytoskeleton under hypotonic stress . We found that in our case, the fast degradation of the vimentin cytoskeleton persisted upon removal of the microtubule cytoskeletal system (Figure S5, Supporting Information).…”
Section: Resultssupporting
confidence: 59%
“…A recent study proposes that microtubule-based transport may mediate the reorganization of the vimentin cytoskeleton under hypotonic stress. [33] We found that in our case, the fast degradation of the vimentin cytoskeleton persisted upon removal of the microtubule cytoskeletal system ( Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 55%
“…[ 33 ] Ubiquitination by gigaxonin, an E3‐ligase targeting factor encoded by the giant axonal neuropathy (GAN) gene also leads to vimentin degradation, and mutations in GAN are associated with the accumulation of VIFs in GAN as well as other types of intermediate filaments in the nervous system. [ 34 ] VIFs are also subject to proteolysis by calpain during osmotic shock [ 35,36 ] and are substrates for some bacterial proteases. [ 37 ] VIFs are also cleaved by calpain during pyroptosis of inflammatory cells.…”
Section: Vimentin Binds To Diverse Cellular Targetsmentioning
confidence: 99%
“…According to the previous work, vimentin presented a more spread and diffuse distribution under hypo-osmotic stress [ 17 ]. This perhaps explains why, in the presence of vimentin, the motion of Cav-1 vesicles induced by hypo-osmosis is further hindered.…”
Section: Resultsmentioning
confidence: 96%
“…Actin-GFP can also be used as a cellular mechanical framework to better characterize the location of Cav-1 vesicles. It is note that, hypo-osmotic stress shows subtle effect to the distribution of actin at least within the initial 5 min [ 17 ]. We also only expressed Cav-1-mCherry without vimentin-GFP or actin-GFP to exclude the effects of overexpressing cytoskeletal proteins to the vesicle motility, the results remained the same (data not shown).…”
Section: Resultsmentioning
confidence: 99%